Exploring medical pluralism as a multifaceted approach to healthcare - Patil, Aditya Dilipkumar; Singh, Sargam; Verma, Dileep; Goupale, Chandrashekar (Indian Journal of Integrative Medicine, 2024)
Medical pluralism, a phenomenon wherein individuals engage with multiple healthcare systems and healing practices, has become an increasingly important area of research within the field of medical anthropology and public health. This research provides an overview of the current state of knowledge in the realm of medical pluralism, highlighting the need for a multidisciplinary approach to better understand its implications on healthcare delivery and outcomes. Medical pluralism is a complex and dynamic interplay of diverse medical systems, such as traditional medicine, complementary and alternative medicine (CAM), and biomedicine, that individuals utilize to address their health needs. The key themes within medical pluralism research, including the cultural, social, and economic factors influencing the choice of healthcare systems, the challenges and opportunities for healthcare integration and collaboration, and the impact of medical pluralism on health disparities and patient outcomes. Furthermore, the abstract emphasizes the importance of bridging the gap between conventional biomedical healthcare and traditional or alternative healing practices. By understanding the diverse ways individuals seek health and healing, researchers and healthcare providers can develop more inclusive and effective healthcare strategies that are sensitive to cultural differences and individual preferences. Additionally, exploring the safety and efficacy of various complementary and alternative therapies within the context of medical pluralism is crucial to ensuring the well-being of patients. The growing significance of medical pluralism in the modern healthcare landscape encourages further research and collaboration between medical anthropologists, healthcare providers, and policymakers. A comprehensive understanding of medical pluralism will aid in the development of healthcare systems that respect and accommodate the diverse healthcare choices of individuals, ultimately leading to more equitable and patient-centered care.